Penerapan Cleanliness, Health, Safety And Environmental Sustainability Pada Penyelenggaraan Kegiatan Wisata Di Keraton Kanoman Cirebon - Widia Ningsi; Toni Ari Wibowo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The spread of Corona Virus Disease (Covid-19) throughout the world causes various impacts in variousfields. In order to anticipate the spread and prevention of Corona Virus Disease (Covid-19), must increase publicawareness of cleanliness, health and safety, change behavior patterns, the tourism world must prepare itself, havestandards for clean, healthy, safe & sustainable products & services..This research activity is a field study by conducting observations and interviews with managers, courtiersand tourists at the Kanoman palace regarding the implementation of Cleanliness, Health, Safety and EnvironmentalSustainability (CHSE) which has been carried out during the adaptation period of new habits (AKB). Theguidelines that have been set are based on guidelines from the Ministry of Tourism and Creative Industries of theRepublic of Indonesia, especially regarding the guidelines for organizing activities.The implementation of Cleanliness, Health, Safety and Environmental Sustainability (CHSE) from thepalace entrance to the facilities provided by the Kanoman Palace is expected that tourists will feel comfortable andsafe and can provide a positive image of the palace in implementing the implementation of Cleanliness, Health,Safety. and Environmental Sustainability (CHSE) whose implementation requires cooperation between variousparties such as managers, employees (servants) and tourists so that Cleanliness, Health, Safety and EnvironmentalSustainability (CHSE) can be implemented and have a positive impact on various parties.